Implementasi Aplikasi Monitoring Suhu dan PH Air Akuarium Berbasis IoT Menggunakan ESP32 - Muh. Awal Nurfajry; Benny Leonard; Imran Iskandar; Watty Rimalia; Untung Suwardoyo (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Water quality is an important factor in maintaining the health and survival of ornamental fish in an aquarium. The main parameters that affect water quality are temperature and acidity level (pH). Manual monitoring of these parameters has limitations; therefore, a monitoring system capable of operating in real time and continuously is required. This study aims to design and implement an Internet of Things (IoT)–based aquarium water temperature and pH monitoring application using an ESP32 microcontroller. The system utilizes a DS18B20 temperature sensor and a pH sensor to measure aquarium water conditions, after which the collected data are transmitted to a Firebase database and displayed on a web-based monitoring dashboard in real time. The research methodology includes system design, hardware and software implementation, and system functionality testing. The results show that the developed system is able to monitor aquarium water temperature and pH accurately and in real time, thereby facilitating users in monitoring water quality. With the implementation of this system, aquarium management is expected to become more effective and to optimally support fish health.